OCCURRENCE OF THE STING RAY DASYATIS (DASYATIS) MICROPS (ANNANDALE) ON THE MADRAS COAST AND IN THE GULF OF MANNAR - Nair, R V; Soundararajan, R (Indian Journal of Fisheries, 2011)
The occurrence of Dasyatis (Dasyctis) microps on the Madras coaM andin the Gulf of Mannar is reported with a brief description of the adults. Theobservations on the male foetus collected from a gravid female is also given